Review Of The Small Scale Gold Mining Practices At Cineam, Tasikmalaya Regency, West Java, Indonesia - Hutamadi Hutamadi; Bambang Nugroho Widi; Sabtanto Joko Suprapto (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2007)
Gold deposit at Cineam area is an epithermal gold deposit of low sulphidation type which lies about 180 km southeast of Bandung at an elevation of 400 meter above the mean sea level. The Cineam deposit is administratively belongs to Cineam Subdistrict , Tasikmalaya Regency, West Java Province, which dominantly occurred within volcanic rocks unit of Jampang Formation. Alterations developed in this area namely propylite, argillic, sericitation, and silisification, occurred in andesitic lava, volcanic breccia, and andesitic to dacitic tuff. The thickness of gold bearing quartz veins are commonly from few cm up to > 20 cm, while for the veins of higher grade of gold content the thickness are about 5 cm or less. The average grade of gold content is around 6 - 10 gr/t Au. Although Cineam gold deposits can not be classified as a big scale deposit, itsmineral genesis has an interesting characteristic to be further studied. The Cineam area representing one of the most prospect areas of gold found in the eastern part of West Java Southern Mountain Range. As the Cineam gold deposit is proportionally suitable for a small scale gold mine, the local government had already gave a mining license to a Family Firm in the form of a Village Unit Cooperation or “KUD” such as KUD Mekarjaya which had also been updated to become a B class of Exploitation License category that permitted for the realization of metallic exploitation. This action was in line with the implementation of Autonomy Policy since the year of 2001.Although KUD Mekarjaya’s mining production is relatively so small but in fact the mining activity is still being maintained to be daily earnings for the local gold miners to rely on. Within the long run of the local gold miners activity at Cineam which has been working since 1968, this condition can give rise to many well skilled and experienced labors in seeking for gold ores, in handling small scale gold mining works, and in obtaining for the bullions. In other side, on thecontrary, there are some negative actions must be kept under control such as the disposal of the waste or tailing directly into the river and the unsafely process of heating the amalgam to obtain the bullion including other improper ways done during the handling of their mining activities. Since the whole mining operation so far generally financed by individual investors it is very likely that small scale gold mining lacks of the capital needed for the mining operation. This condition is what the KUD always facing with so that management and financial matters can be a very serious problem affecting the progress of the KUD Mekarjaya From some presentation given by the CCOP-CASM Meeting in Bandung we can compare the condition of small scale mining in Indonesia. and that from other countries which have conducted good management in mining regulation and policy in relation with licensing, mining workers, tax payment and awareness of environment live in the vicinity of mining areas On account of that event this can be expected to motivate and encourage the policy anddecision makers either locally or centrally throughout Indonesia in giving more attention related to the guidance, monitoring and inspection of the implementation of small scale mining activities which is actually growing in numbers.